Ten questions concerning energy flexibility in buildings - Li, Rongling (2022)
Danish Energy Agency for supporting the Danish delegates participating IEA EBC Annex 82 through EUDP (grant number 64020-2131 ); Innovation Fund Denmark in relation to SEM4Cities ( IFD 0143–0004 ) and Flexible Energy Denmark ( IFD 8090-00069B ); the Building Technologies Office, Office of Energy Efficiency and Renewable Energy, at the US Department of Energy , under Lawrence Berkeley National Laboratory (contract number DE-AC02-05CH11231 ); Research Council of Norway in relation to Research Centre on Zero Emission Neighborhoods in Smart Cities - FME-ZEN (No. 2576609 ) and FlexBuild (No. 294920 ); the AGAUR Agency from the Generalitat de Catalunya through the project ComMit-20 ( 2020PANDE00116 ); the National Science and Engineering Research Council of Canada (NSERC Discovery Grant RGPIN 2016-06643 ). Publisher Copyright: © 2022 The Authors